Evaluation of the impact of time-dependent compaction, induced stress and spacing on stability for deep cave mines - Fuenzalida, M; Paredes, P (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
In deep, high-column caving operations, the robustness and reliability of the extraction level is paramount to withstand the geotechnical challenges associated with higher stress. Larger-pillar footprint layouts offer potential advantages such as improved extraction level pillar stability and reduced development scope. However, these configurations can also reduce overall recovery, as the larger drawpoint spacing increases the height of the stagnant zones. During cave establishment, isolated flow zones may form squat-shaped stagnant zones above drawpoint apices. If insufficient swell tonnage is extracted during undercutting, stagnant zones of broken material can persist between the top of the undercut and the extraction level, enabling transfer of high vertical stresses to the extraction level and increasing the risk of local instabilities. Additionally, as spacing increases, layouts may be more exposed to stress build-up from cave loads during extended draw cessation periods. This study examines the influence of induced stresses and spacing on extraction level stability using an enhanced numerical modelling workflow that captures key mechanical processes in caved material, including time-dependent compaction, modulus softening/hardening and rock mass strength degradation. Two footprint configurations (32 × 20 m and 35 × 22 m), two production ramp-up strategies and two rock mass strength conditions (moderate and weak) were assessed. Results indicate that the larger-pillar layout generally improves extraction level stability compared to the narrower configuration. However, increased vertical stress from time-dependent compaction during draw cessation can lead to localised instabilities in weaker rock masses, even for the larger-pillar layout case. These findings highlight the need to balance layout spacing and production scheduling to manage stress evolution and maintain long-term extraction level performance.
Keywords: footprint stability; cave mining; induced stress; numerical modelling; time-dependent compaction